Development of Multifunctional Polydopamine Nanoparticles As a Theranostic Nanoplatform against Cancer Cells - Wang, Jingjing (Langmuir : the ACS journal of surfaces and colloids, 2018)
Although demanding, the development of multifunctional theranostic nanoplatforms is attracting considerable worldwide interest. Herein, a theranostic nanoplatform with multifunctions based on polydopamine (PDA) nanoparticles (NPs) was developed, owning dual-imaging and dual-therapy functions for cancer theranostic applications. PDA NPs were generated using a facile polymerization method under alkaline conditions, followed by poly(ethylene glycol) (PEG) modification. Then, the obtained NPs were loaded with IR820 and Fe3+ ions to produce the final PEGylated PDA/IR820/Fe3+ (PPIF) NPs. The PPIF NPs thus generated displayed increasingly brighter photoacoustic and magnetic resonance signals with increasing NP concentration and were demonstrated to be cytocompatible and effectively taken up and internalized into HeLa cells. Under near-infrared light irradiation, PPIF NPs can produce heat and reactive oxygen species for photothermal/photodynamic combined cancer therapy. In this study, the versatility of PDA NPs was demonstrated to be promising as a multifunctional nanoplatform for potential cancer theranostic applications